Reliance on Russian Federation Energy Imports and Renewable Energy in the European Union - Anca Gabriela Ilie; Marinela Luminita Emanuela Zlatea; Cristina Negreanu; Dan Dumitriu; Alma Pentescu (Amfiteatru Economic, 2023)
The paper investigates the importance of renewable energy in the energy mix of EU-27 countries, as well as their dependence on imports of gas, oil and petroleum products from the Russian Federation, considering the long-term energy security of the EU-27, as well as the objectives of the RePowerEU plan. The article divides EU countries into two groups using a clustering algorithm, revealing that Central and Eastern European countries share similar characteristics in terms of their reliance on Russian energy imports and energy mix, while Western European countries show significant variation between group members. Cluster analysis is complemented by an investigation using the Random forests methodology based on machine-learning algorithms, which highlights the importance of variables for grouping countries into clusters. Surprisingly, Eastern European countries have a higher proportion of renewable energy sources in their energy mix than most Western European countries, which could be attributed to their recent efforts to find alternatives to Russian energy imports. At the same time, the lack of interconnected infrastructure between EU member states is a significant contributor to the bloc's reliance on Russian Federation energy imports, as evidenced by cases in Finland, Bulgaria, and Hungary.
Keywords: Q20; Q30; C38; N54; 330; import dependency; energy mix; renewable energy; cluster analysis; European Union; REPowerEU.